The Effect Of Puzzle Playing Therapy On Anxiety Due To The Impact Of Hospitalization In Preschool Aged Children: Study Literature Review: Pengaruh Terapi Bermain Puzzle Terhadap Kecemasan Akibat Dampak Hospitalisasi Pada Anak Usia Prasekolah: Study Literature Review - Fadhilah, Vita; Wardani, Septi; Mareta, Reni (Prosiding University Research Colloquium, 2024)
Background: Hospitalization can cause anxiety in some children. The level of anxiety due to hospitalization in most preschool-age children is moderate to severe anxiety. Puzzle play therapy is a therapy that can reduce anxiety in preschool-aged children. Purpose: Identify anxiety due to hospitalization in preschool-aged children before and after playing puzzle therapy, identify the effect of playing puzzle therapy on hospitalization anxiety in preschool-aged children. Method: The method used in this study was a literature review design by collecting secondary data from Google Scholar and ScientDirect using the keywords "Preschool-aged children AND puzzle play therapy AND anxiety of hospitalization", as many as 9 articles that met the inclusion criteria with the publication year range 2019-2023. Results: The anxiety experienced by preschool-aged children at the time of hospitalization before being given puzzle play therapy experienced mild-severe anxiety, and after being given puzzle play therapy the child’s anxiety level decreased to mild-moderate anxiety. Conclusion: this proves that there is an effect of playing puzzle therapy to reduce anxiety levels in preschool-aged children due to hospitalization.